2011
DOI: 10.1007/s13149-011-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

Discharge of children against medical advice at CHU of Brazzaville (Congo)

Abstract: In a prospective study conducted from January to December 2010 in the Teaching Hospital of Brazzaville (Congo), we compared the discharge of hospitalized children against medical advice at the parents' request (group 1 - cases) with those admitted during same period with routine discharge (group 2 - controls). Two hundred and seven (7.7%) hospitalized children, 117 boys and 90 girls, were discharged at the parents request. The mean age was 18.0 ± 13.5 months (range: 1 month-5 years). Among these patients, 150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
3
1
Order By: Relevance
“…While one study has shown that the children of parents who were satisfied with their jobs spend more time in the hospital receiving treatment, 27 our investigation concluded that a parent's occupation did not play a role in the level of the completion of their child's medical treatment. Aliyu et al 26 . showed that patients who experienced long periods of treatment and hospitalisation had a greater tendency to insist on DAMA, which was confirmed by the present study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…While one study has shown that the children of parents who were satisfied with their jobs spend more time in the hospital receiving treatment, 27 our investigation concluded that a parent's occupation did not play a role in the level of the completion of their child's medical treatment. Aliyu et al 26 . showed that patients who experienced long periods of treatment and hospitalisation had a greater tendency to insist on DAMA, which was confirmed by the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Economic factors are the most important factors in early clearance with personal satisfaction. While Aliyu et al 26 . showed that economic issues were the most important factors for DAMA, we did not find this in our research; although, this may be because our population displayed values of promoting health and a high rate of insurance coverage 23 .…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…In studies conducted in African hospitals, most authors have found high proportions of discharges without or against medical advice. The main reasons for these discharges were the lack of improvement in health, nancial di culties, poor hospital conditions and disagreements with caregivers (14).…”
Section: Discussionmentioning
confidence: 99%